Do peers affect student achievement in China's secondary schools? - Weili Ding; Steven F. Lehrer (Queen's University, Department of Economics, 2006)
Peer effects have figured prominently in debates on school vouchers, desegregation, ability tracking and anti-poverty programs. Compelling evidence of their existence remains scarce for plaguing endogeneity issues such as selection bias and the reflection problem. This paper is among the first to firmly establish the link between peer performance and student achievement, using a unique dataset from China. We find strong evidence that peer effects exist and operate in a positive and nonlinear manner; reducing the variation of peer performance increases achievement; and our semi-parametric estimates clarify the tradeoffs facing policymakers in exploiting positive peers effects to increase future achievement.
Keywords: I2; P36; Z13; 330; Peer Effects; Ability Grouping; Selection on observables; China; Academic performance; Teacher quality; Bildungswesen; Allgemeinbildende Schule; Bildungsverhalten; Soziale Beziehungen; Soziales Netzwerk; China